2021
DOI: 10.2147/ijwh.s303568
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Education on Dietary Knowledge and Practices of Pregnant Women in Jordan: A Quasi-Experimental Study

Abstract: Background Evidence reported inadequate dietary practices among pregnant women and recommended educating pregnant women about their diet to improve pregnancy outcomes. However, studies examining the effect of health education about dietary practices during pregnancy are lacking in Jordan. Objective To examine the effect of health education on the levels of dietary knowledge and practices among pregnant women in Jordan. Methods A quasi-experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The population size ranged from 47 in Villalon et al (2010) to 2230 in Belizan et al (1995). Thirty‐eight studies described the participant characteristics by at least one element of PROGRESS‐+ (Abdel‐Aziz et al, 2018; Abu‐Baker et al, 2021; Kiani Asiabar et al, 2018; Aşcı & Rathfisch, 2016; Belizan et al, 1995; Daniel et al, 2016; Demilew et al, 2020; Garg & Kashyap, 2006; Goodarzi‐Khoigani et al, 2018; Hasneezah et al, 2020; Isrctn, 2017; Izadirad et al, 2017; Jahan et al, 2014; Jing et al, 2015; Kafatos et al, 1989; Kamalifard et al, 2012; Kanber et al, 2011; Katenga‐Kaunda et al, 2021; Khoramabadi et al, 2015; Kian et al, 2016; Lin et al, 2020; Liu et al, 2017; Malta et al, 2021; Mirmolaei et al, 2009; Mohsenzadeh‐Ledari et al, 2020; Nahrisah et al, 2020; Nyamasege et al, 2021; Nyamasege et al, 2018; Perichart‐Perera et al, 2009; Permatasari et al, 2021; Saadatnia et al, 2021; Sharifirad et al, 2013; Sunuwar et al, 2019; Tu et al, 2021; Villalon et al, 2010; Zhou & Tang, 2020; Ziyenda Katenga‐Kaunda et al, 2020). Thirty‐six studies (84%) reported the age of the pregnant women (Abu‐Baker et al, 2021; Kiani Asiabar et al, 2018; Aşcı & Rathfisch, 2016; Belizan et al, 1995; Daniel et al, 2016; Demilew et al, 2020; Garg & Kashyap, 2006; Goodarzi‐Khoigani et al, 2018; Hasneezah et al, 2020; Isrctn, 2017; Izadirad et al, 2017; Jahan et al, 2014; Jing et al, 2015; Kafatos et al, 1989; Kamalifard et al, ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The population size ranged from 47 in Villalon et al (2010) to 2230 in Belizan et al (1995). Thirty‐eight studies described the participant characteristics by at least one element of PROGRESS‐+ (Abdel‐Aziz et al, 2018; Abu‐Baker et al, 2021; Kiani Asiabar et al, 2018; Aşcı & Rathfisch, 2016; Belizan et al, 1995; Daniel et al, 2016; Demilew et al, 2020; Garg & Kashyap, 2006; Goodarzi‐Khoigani et al, 2018; Hasneezah et al, 2020; Isrctn, 2017; Izadirad et al, 2017; Jahan et al, 2014; Jing et al, 2015; Kafatos et al, 1989; Kamalifard et al, 2012; Kanber et al, 2011; Katenga‐Kaunda et al, 2021; Khoramabadi et al, 2015; Kian et al, 2016; Lin et al, 2020; Liu et al, 2017; Malta et al, 2021; Mirmolaei et al, 2009; Mohsenzadeh‐Ledari et al, 2020; Nahrisah et al, 2020; Nyamasege et al, 2021; Nyamasege et al, 2018; Perichart‐Perera et al, 2009; Permatasari et al, 2021; Saadatnia et al, 2021; Sharifirad et al, 2013; Sunuwar et al, 2019; Tu et al, 2021; Villalon et al, 2010; Zhou & Tang, 2020; Ziyenda Katenga‐Kaunda et al, 2020). Thirty‐six studies (84%) reported the age of the pregnant women (Abu‐Baker et al, 2021; Kiani Asiabar et al, 2018; Aşcı & Rathfisch, 2016; Belizan et al, 1995; Daniel et al, 2016; Demilew et al, 2020; Garg & Kashyap, 2006; Goodarzi‐Khoigani et al, 2018; Hasneezah et al, 2020; Isrctn, 2017; Izadirad et al, 2017; Jahan et al, 2014; Jing et al, 2015; Kafatos et al, 1989; Kamalifard et al, ...…”
Section: Resultsmentioning
confidence: 99%
“…We included a total of 42 studies for nutrition counseling to improve maternal and infant outcomes. Nineteen studies were RCTs (Abdel‐Aziz et al, 2018 ; Asiabar et al, 2018 ; Aşcı & Rathfisch, 2016 ; Belizan et al, 1995 ; Goodarzi‐Khoigani et al, 2018 ; Izadirad et al, 2017 ; Jahan et al, 2014 ; Jahangiri et al, 2020 ; Jing et al, 2015 ; Kanber et al, 2011 ; Khoramabadi et al, 2015 ; Kian et al, 2016 ; Lin et al, 2020 ; Liu et al, 2009 ; Mazloomy‐Mahmoodabad et al, 2020 ; Mohsenzadeh‐Ledari et al, 2020 ; Tu et al, 2021 ; Vítolo et al, 2011 ; Zhou & Tang, 2020 ), 16 were NRS (Abu‐Baker et al, 2021 ; Daniel et al, 2016 ; Garg & Kashyap, 2006 ; Hasneezah et al, 2020 ; Kamalifard et al, 2012 ; Liu et al, 2017 ; Malta et al, 2021 ; Mirmolaei et al, 2009 ; Nahrisah et al, 2020 ; Perichart‐Perera et al, 2009 ; Permatasari et al, 2021 ; Saadatnia et al, 2021 ; Sachdeva & Mann, 1994 ; Sharifirad et al, 2013 ; Sunuwar et al, 2019 ; Villalon et al, 2010 ) and 7 were CRTs (Demilew et al, 2020 ; Isrctn, 2017 ; Kafatos et al, 1989 ; Katenga‐Kaunda et al, 2021 ; Nyamasege et al, 2021 ; Nyamasege et al, 2018 ; Ziyenda Katenga‐Kaunda et al, 2020 ). All the studies compared two‐way interactive nutrition counseling with standard ANC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations